Stackable 3D-printed core-shell nozzle system for multi-shell fiber and microdroplet generation - Li, Jianfeng; Fischer, Peer (Materials and design, 2025)
Microfluidics is increasingly utilized in biofabrication to create more complex fiber and droplet structures, including those that involve multiple materials. Layered and core-multiple shell structures are of particular interest as templates for biofabrication and cell growth. Traditional fabrication methods often rely on fixed coaxial, triaxial or quadaxial needles, which are costly and prone to clogging, particularly for smaller inner diameters. Here, we introduce a versatile system based on a 3D printed nozzle which combines two flows: an inner core- and an outer shell-flow. The outlet is fitted with a glass capillary, allowing control of the fiber diameter by adjusting the capillary. The design facilitates the modular “LEGO®-Brick” stacking of multiple nozzles, enabling the efficient fabrication of complex fibers. We demonstrate the production of alginate (Alg)-methyl cellulose (MC) composite fibers with variable diameters. Additionally, when the shell was filled with an oil phase and the core with a water phase, microdroplets with controlled diameters were effectively generated. The two-flow system also enables the extrusion of graphene oxide (GO)-based fibers and microbeads, which are widely-used structures in various applications. To demonstrate the capability of the designed nozzle for biofabrication, C2C12 cell-laden GO-based fibers and microbeads were fabricated, exhibiting excellent post-fabrication cell viability.